Glycaemic control status among type 2 diabetic patients and the role of their diabetes coping behaviours: a clinic-based study in Tripoli, Libya. Issue 1 (1st January 2016) - Ashur, Sana Taher; Shah, Shamsul Azhar; Bosseri, Soad; Fah, Tong Seng; Shamsuddin, Khadijah
Abstract : Background: Achieving good glycaemic control is important in diabetes management. However, poor glycaemic control is widely reported. This article assessed the prevalence of uncontrolled and poor glycaemic control among Libyans with type 2 diabetes and examined the relative contribution of diabetes coping behaviours to their glycaemic control status. Methods: A cross-sectional study was undertaken in 2013 in a large diabetes centre in Tripoli. The study included 523 respondents. Diabetes coping behaviours were measured using the revised version of the Summary of Diabetes Self-Care Activities measure (SDSCA) and the eight-item Morisky Medication Adherence Scale (MMAS-8 © ), while glycaemic control status was based on the HbA1c level. Results: Mean HbA1c was 8.9 (±2.1), and of the 523 patients, only 114 (21.8%) attained the glycaemic control target of HbAc1 of less than 7.0%. Females (OR=1.74, 95% CI=1.03–2.91), patients on insulin and oral hypoglycaemic agents (OR=1.92, 95% CI=1.05–3.54), patients on insulin (OR=3.14, 95% CI=1.66–6.03), and low-medication adherents (OR=2.25, 95% CI=1.36–3.73) were more likely to have uncontrolled and poor glycaemic control, while exercise contributed to glycaemic control status as a protective factor (OR=0.85, 95% CI=0.77–0.94). Conclusion: The findings from this study showed the considerable burden of uncontrolled and poor glycaemic control in one of the largest diabetes care settings in Libya. Medication adherence as well as exercise promotion programs would help in reducing the magnitude of poor glycaemic control.